P14.43 Histone H3F3A and HIST1H3B K27M mutations in pediatric high-grade gliomas: the Florentine experience. (6th September 2019) - Guidi, M
Abstract: Background: Pediatric high- grade gliomas (HGGs) represent a malignancy with a poor survival. The genetic analysis of these entities has identified useful mutations for an improved prognostic framing. The research of mutations in all H3 histone variants (HIST1H3B and H3F3A) could be usefull to define tumors with different prognosis and phenotypes inasmuch they seems to drive two distinct oncogenic programmes. MATERIALS E METHODS: We performed a retrospective analysis of pediatric HGGs. We evaluated the type of histone H3 mutated and we performed a meta-analysis comparing our results with literature data. RESULTS: We evaluated 41 cases of pediatric HGGs (median age of patients: 7 years old, range: 0–32):): 32 anaplastic astrocytoma (78, 5%), 9 glioblastoma multiforme (25, 9%), We have researched the K27M mutations in the distinct histone H3 variants (i.e. HIST1H3B and H3F3A). The mutation H3F3A K27M was found in 6 patients instead HIST1H3B K27 mutations was found in a single patient with GBM. All the patients with H3F3A K27M mutation had a progression disease but without statistical correlation (p:0, 07). They had a worse prognosis with a median overall survival of 15, 5 months (p: 0.0014) versus wild type patients (not reached). H3.3K27M mutation status is a signiﬁcant predictor of OS with a hazard ratio of 4.499 (p = 0.0001). The patient with HIST1H3B K27 mutation died after first line of therapy. Conclusions: Due to the low incidence of the mutation HIST1H3B in our series we can't define the difference with two variants. However, the research of K27M mutation in HGGs has diagnostic and prognostic role. The role of histone H3 mutated could predict the outcome in HGGs patients and it could give us more informations compared to the clinic and radiological characteristic of the tumors.